Political Activism and Firm Innovation - Ovtchinnikov, Alexei V.; Reza, Syed Walid; Wu, Yanhui (Journal of Financial and Quantitative Analysis, 2020)
We hypothesize that political activism is valuable because it helps reduce political uncertainty, which, in turn, fosters firm innovation. We find that firms that support more politicians, winning politicians, politicians on congressional committees with jurisdictional authority over the firms’ industries, and politicians who join those committees innovate more. We employ a natural experiment to show a causal effect of political activism on innovation. We also show evidence of intra-industry and geographical political activism spillovers.